Microwave Processing of High Temperature Materials-An Overview - Babu, Sanjesh; Govindan, Anil (Asian Journal of Chemistry, 2011)
Microwave processing of ceramics and composites is a relatively new technology alternative that provides new approaches for enhancing material properties as well as economic advantages through energy savings and accelerated product development. Over the last two decades, microwave energy is being increasingly applied in the area of a ceramics and composites processing for various purposes. Remarkable achievements have been made in the sintering and synthesis of ceramics and composites using microwaves. In the last decade, many significant developments and advances have taken place in the field of microwave processing of materials. Microwave technology have been used for important ceramics materials i.e., Al2O3, ZrO2, lead zirconate titanate, BaTiO3, multilayer ceramic capacitors, transparent ceramics, CaCu3Ti4O12, tungsten carbide-cobalt based ceramic-metal composites etc. In this article, microwave sintering technique of high temperature materials has been reviewed.